EPIGENETIC MECHANISMS OF TISSUE AGING. (20th December 2022) - Sen, Payel; Yang, Na; Occean, James; Melters, Daniel; Shi, Changyou; Wang, Lin; Sidoli, Simone; Dalal, Yamini
Abstract: Epigenetic alterations are one of the key hallmarks of aging. How epigenetic changes broadly affect euchromatin-heterochromatin balance, three-dimensional chromatin conformation, histone composition and global transcriptome in aging have not been addressed. Using murine liver as a model organ and an integrated multi-omics approach, we find that aged cells assume a repressed chromatin state characterized by condensed chromatin, broad heterochromatinization, global suppression of the transcriptome, and inability to self-interact over long distances. Our findings reveal that global chromatin alterations pose a barrier and promote a cellular state that is refractory to injury sensing and repair.